Deschloroclozapine exhibits an exquisite agonistic effect at lower concentration compared to clozapine-N-oxide in hM3Dq expressing chemogenetically modified rats - Shimizu, Makiko; Yoshimura, Mitsuhiro; Baba, Kazuhiko; Ikeda, Naofumi; Nonaka, Yuki; Maruyama, Takashi; Onaka, Tatsushi; Ueta, Yoichi (Frontiers in Neuroscience, 2023)
Introduction Within the realm of chemogenetics, a particular form of agonists targeting designer receptors exclusively activated by designer drugs (DREADDs) has emerged. Deschloroclozapine (DCZ), a recently introduced DREADDs agonist, demonstrates remarkable potency in activating targeted neurons at a lower dosage compared to clozapine-N-oxide (CNO). Methods We conducted a comparative analysis of the effects of subcutaneously administered CNO (1 mg/kg) and DCZ (0.1 mg/kg) in our transgenic rats expressing hM3Dq and mCherry exclusively in oxytocin (OXT) neurons. Results and Discussion Notably, DCZ exhibited a swift and robust elevation of serum OXT, surpassing the effects of CNO, with a significant increase in the area under the curve (AUC) up to 3 hours post-administration. Comprehensive assessment of brain neuronal activity, using Fos as an indicator, revealed comparable effects between CNO and DCZ. Additionally, in a neuropathic pain model, both CNO and DCZ increased the mechanical nociceptive and thermal thresholds; however, the DCZ-treated group exhibited a significantly accelerated onset of the effects, aligning harmoniously with the observed alterations in serum OXT concentration following DCZ administration. These findings emphasize the remarkable efficacy of DCZ in rats, suggesting its equivalent or potentially superior performance to CNO at considerably lower dosages, thus positioning it as a promising contender among DREADDs agonists.